Inflammation in cancer and depression: a starring role for the kynurenine pathway - Sforzini, Luca; Nettis, Maria Antonietta; Mondelli, Valeria; Pariante, Carmine Maria (Psychopharmacology, 2019)
Depression is a common comorbidity in cancer cases, but this is not only due to the emotional distress of having a life-threatening disease. A common biological mechanism, involving a dysregulated immune system, seems to underpin this comorbidity. In particular, the activation of the kynurenine pathway of tryptophan degradation due to inflammation may play a key role in the development and persistence of both diseases. As a consequence, targeting enzymes involved in this pathway offers a unique opportunity to develop new strategies to treat cancer and depression at once. In this work, we provide a systematic review of the evidence up to date on the kynurenine pathway role in linking depression and cancer and on clinical implications of this evidence. In particular, complications due to chemotherapy are discussed, as well as the potential antidepressant efficacy of novel immunotherapies for cancer.